2013
DOI: 10.1073/pnas.1308997110
|View full text |Cite
|
Sign up to set email alerts
|

Out of the tropics, but how? Fossils, bridge species, and thermal ranges in the dynamics of the marine latitudinal diversity gradient

Abstract: Latitudinal diversity gradients are underlain by complex combinations of origination, extinction, and shifts in geographic distribution and therefore are best analyzed by integrating paleontological and neontological data. The fossil record of marine bivalves shows, in three successive late Cenozoic time slices, that most clades (operationally here, genera) tend to originate in the tropics and then expand out of the tropics (OTT) to higher latitudes while retaining their tropical presence. This OTT pattern is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
220
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(246 citation statements)
references
References 94 publications
21
220
4
1
Order By: Relevance
“…Further, the diversity differences among the regionally dominant families are not correlated with Pliocene−Recent extinction intensities, indicating that post-Pliocene speciation and immigration were also involved in shaping present-day biotas. Such a scenario is consistent with previous suggestions (3,40) that the milder temperature gradients along the W Atlantic owing to the northward flow of the Gulf Stream have been more conducive to northward expansion of species over the past 5 My (the E Pacific receives cool water via the California Current and localized upwelling, both potential barriers to the northward spread of species). This hypothesized contrast in the biotic dynamics of western and eastern boundaries of ocean basins, with a stronger flow of species and clades out of the tropics in the W Atlantic, may account for the rapid recovery of diversity in that region, even as in situ diversification rates in the Caribbean left its diversity lagging behind that in the tropical E Pacific.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, the diversity differences among the regionally dominant families are not correlated with Pliocene−Recent extinction intensities, indicating that post-Pliocene speciation and immigration were also involved in shaping present-day biotas. Such a scenario is consistent with previous suggestions (3,40) that the milder temperature gradients along the W Atlantic owing to the northward flow of the Gulf Stream have been more conducive to northward expansion of species over the past 5 My (the E Pacific receives cool water via the California Current and localized upwelling, both potential barriers to the northward spread of species). This hypothesized contrast in the biotic dynamics of western and eastern boundaries of ocean basins, with a stronger flow of species and clades out of the tropics in the W Atlantic, may account for the rapid recovery of diversity in that region, even as in situ diversification rates in the Caribbean left its diversity lagging behind that in the tropical E Pacific.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that such data may be crucial for understanding their apparent contrast in evolutionary dynamics. More generally, our analyses add to the wide array of studies that have drawn a richer understanding from the geologic record into the nature and origins of present-day diversity patterns (3,4,6,25,36,51,55).…”
Section: Discussionmentioning
confidence: 94%
“…We show that large-scale parameters of species' niches, in this case temperature and salinity, do not change for a phylogenetically and ecologically diverse set of marine molluscs. Although species may modify their behaviour or resource utilization, the FN places constraints on species' interactions with the environment, which potentially governs speciation and extinction processes over long time scales [10,89]. Some researchers have suggested that niche stability may promote allopatric speciation [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…Given these changes, debate exists as to whether species can adapt their physiological tolerances, or niches, to altered environmental conditions [1][2][3][4]. Determining whether species' niches evolve or remain stable in the face of environmental change is important for implementing proper conservation measures, mitigating threats posed to biodiversity [5][6][7] and shedding light on macroevolutionary dynamics [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We compiled 60 942 occurrence records of marine bivalves (5 903 species in 1 073 genera) occurring at depths less than 200 m from the literature and museum collections [34]. Species occurrences were resolved to a median latitudinal and longitudinal resolution of around 18.…”
Section: Materials and Methods (A) Bivalvesmentioning
confidence: 99%